2006
DOI: 10.1002/for.984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two non‐parametric models for daily traffic forecasting in Hong Kong

Abstract: The most up-to-date annual average daily traffic (AADT) is always required for transport model development and calibration. However, the current-year AADT data are not always available. The short-term traffic flow forecasting models can be used to predict the traffic flows for the current year. In this paper, two non-parametric models, non-parametric regression (NPR) and Gaussian maximum likelihood (GML), are chosen for short-term traffic forecasting based on historical data collected for the annual traffic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 9 publications
0
21
0
1
Order By: Relevance
“…Considering the simplicity of the parametric techniques and the proved facts that nonparametric regression (NPR) performs better than the parametric counterpart [4][5] , we choose both parametric and nonparametric techniques in this work. Representative forecasting methods are investigated for the performance comparison as follows: historical-mean (HM), ARMA, Kalman filtering (KF), linear regression (LR), RBF networks and SVR models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the simplicity of the parametric techniques and the proved facts that nonparametric regression (NPR) performs better than the parametric counterpart [4][5] , we choose both parametric and nonparametric techniques in this work. Representative forecasting methods are investigated for the performance comparison as follows: historical-mean (HM), ARMA, Kalman filtering (KF), linear regression (LR), RBF networks and SVR models.…”
Section: Introductionmentioning
confidence: 99%
“…Lately extraordinary development of distinct nonparametric techniques, including nonparametric regression, neural networks, etc., has shown that their great potential alternative to their parametric counterparts. In essence, nonparametric statistical regression can be regarded as a dynamic clustering model that relies on the relationship between dependent and independent traffic variables [4][5] . In other words, it attempts to identify past information that is similar to the state at prediction time, and leads to easily implemented nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the scenario of pedestrian quantity estimation, we directly model the edgeoriented quantities [5,6,15] within a Gaussian process regression framework. First, we convert the original networkG(Ṽ,Ẽ) to an edge graph G(V, E) that represents the adjacencies between edges ofG.…”
Section: Gpr With Trajectory Patternsmentioning
confidence: 99%
“…Improvements of this technique were achieved by respecting the geographical space by usage of geographical weighted regression (GWR) [4] and by application of k-nearest neighbor approaches (kNN) [5]. In [6] the AADT prediction of kNN for a particular location is improved by weighting measurements by their temporal distance to the prediction time. This approach showed better results than application of Gaussian maximum likelihood (GML) approaches for weighting of the historical data points.…”
Section: Related Workmentioning
confidence: 99%